ךאפרײינא A Short Note on ἐγώ εἰμι Sayings and the Dangers of a Translation Tradition - Wollenberg, Rebecca Scharbach (2017)
It is sometimes debated whether the absolute “I am” sayings in the Gospel of John should be read as a claim to divinity, in light of their similarity to the Hebrew text of Exod 3:14. What has not been recognized is that the Johannine “I am” sayings with predicate nominatives also echo the Hebrew Bible text, which includes an extensive collection of verses in which God uses the phrase “I am” with a predicate nominative. This essay offers an analysis of a selection of these Hebrew Bible parallels and proposes an explanation for why this connection has gone unremarked until now.
Keywords: Bibel; Bibel; Übersetzung; Hebräisch; Griechisch; Gospel of John -- “I am” sayings -- Hebrew Bible -- background -- lxx